Efficacy of Esthetic Retainers: Clinical Comparison between Multistranded Wires and Direct-Bond Glass Fiber-Reinforced Composite Splints - Andrea Scribante; Maria Francesca Sfondrini; Simona Broggini; Marina D'Allocco; Paola Gandini (International Journal of Dentistry)
The purpose of this longitudinal prospective randomized study was to evaluate the reliability of two different types of orthodontic retainers in clinical use: a multistrand stainless steel wire and a polyethylene ribbon-reinforced resin composite. Moreover the level of satisfaction of the patient about the esthetic result was also analyzed by means of a Visual Analogue Scale (VAS). 34 patients (9 boys and 25 girls, mean age 14.3), in the finishing phase of orthodontic treatment, were selected for the study. Since splints were applied the number, cause, and date of splint failures were recorded for each single tooth over 12 months. Statistical analysis was performed using a paired 𝑡-test, Kaplan Meier survival estimates, and the log-rank test. Kruskal Wallis test was performed to analyze VAS recordings. Differences between the bond failure rates were not statistically significant. Esthetic result of VAS was significantly higher for polyethylene ribbon-reinforced resin retainers than for stainless steel wires.